Estado de los tratados y convenciones Interamericanos = Status of Inter-American treaties and conventions = Relação dos tratados e convenções Interamericanos = État des traités et des conventions Interaméricains / Pan American Union. General Legal Division. - Organization of American States. General Secretariat.; Pan American Union. General Legal Division. (Tufts University. Tisch Library., 2017)
1 online resource (volumes); Vols. for <1973-> issued by: Organization of American States, General Secretariat.; Tisch Outsourced Digitization 2017-10-02